Usuarios de información pública de la ciudad de Jaén (1976-1996) - Santaella Ruiz, Rita Dolores (Revista General de Información y Documentación, 2008)
Taking as source of intelligence more than 13,000 consultations carried out by Administration public to his archives and requests made by investigators, present article shows yield of file, since it is source of intelligence as much for the organism that generates it, like for the citizenship in general, investigators in individual and the coming generations like source of intelligence of official history. In addition to the definition of the profile of users of the Provincial Historical File of Jaén, Municipal File of Jaén and the File of Provincial Delegation, contributes the definition of these investigations, the objectives that are tried to obtain, the used methodology, the location of these quantitative techniques in the technical subsystem, like powerful tool for its evaluation, conclusions destined to the promotion of these studies, doing emphasis in the importance of the Documentation like science applied to other disciplines, and an extensive bibliography for the theoretical elaboration of investigations of these characteristics.